Haemostatic abnormalities in solid malignancies - Joshi, Supriya D.; Murdeshwar, Hemant G.; Pandit, Gopal A. (International Journal of Research in Medical Sciences, 2018)
Background: Though the actual symptoms of any haemostatic abnormalities in patients of solid malignancies are not seen commonly screening in all such cases can guide us to correct those abnormalities in time and improve the outcome. The present study is undertaken with an objective to find out coagulation disorders in patients of solid malignancies and compare their levels according to the stage of the cancer. Methods: A prospective study was undertaken in a tertiary care centre in Maharashtra, India from December 2010 to September 2012. Total 102 cases with malignancies diagnosed on histopathology/cytological examination were tested for BT, CT, Platelet count, PT, APTT, TT and D-dimer levels. These tests were repeated on first postoperative or post chemotherapy day wherever possible. Early and advanced stages of cancer were divided according to the spread of the tumor. Results were compared between the two. DIC cases were also noted. Results: Out of 102 cases studied, haemostatic abnormalities were more common in adenocarcinomas that too in mucin secreting adenocarcinomas. The percentage of cases with increased D-dimer values was higher in the advanced disease compared to early disease. The PT, APTT, TT and platelet count showed statistically significant differences between the early and advanced disease groups. Compared to preoperative values, postoperative values were abnormal but the change was not statistically significant. Conclusions: Screening for coagulation profile in all solid malignancies can help to predict the chances of complication and therapeutic interventions can be done.